Reaktualisasi Nilai Sosial Budaya Melalui Pendidikan Dan Pembentukan Karakter Bangsa Di Sekolah - Jumadi Jumadi (Jurnal Pendidikan Sejarah, 2015)
Character education is one of the answers to the formation of national character. Character education has become a mission in an effort to realize the vision of national development. Design education and character formation in macro is done through the process of planning, implementation, and evaluation of outcomes involving all sectors of life, while the micro constructed and formed in the four pillars of teaching and learning activities in the classroom, activities of daily life in the form of cultural education unit, the activities co-curricular and extra-curricular and daily activities at home and in the community.